Making race, making power : North Carolina's road to disfranchisement - Redding, Kent, 1962- (University of Illinois Press, 2003)
"In this work, Kent Redding examines the fluid political landscape of the nineteenth-century South, revealing the complex interplay between the elites' manipulation of political and racial identity and the innovative mobilizing strategies marginalized groups adopted to combat disfranchisement." "Redding reveals how the ruling class operated with motivations and methods very similar to those of the black voters and Populist farmers they fought against. He deftly tracks how the elites co-opted the innovative mobilizing strategies of the subaltern groups to effectively use their own weapons against them."--Jacket